Barrierefreie Theologie: Herausforderungen durch Ulrich Bach - Krauß, Anne (2010)
Protestant pastor and theologian Ulrich Bach (1931–2009) developed his specific theology from the wheelchair. This work provides a synopsis of his theological concepts on the Handicapped in the context of the Disability Studies. Bach’s critical perspective on the treatment of handicapped per-sons in society, theology, church and the social service arm of the protestant clergy is examined in the first part. The second section of this thesis investigates Bach’s concept of a „barrier-free theology“ in terms of homiletics and bibliodrama and discusses its practical application in theology and hermeneutics.